Correlation of obesity and osteoporosis: Effect of free fatty acids on bone marrow-derived mesenchymal stem cell differentiation - LV, SHAN (D.A. Spandidos, 2010)
Studies on the relationship between obesity and bone have recently become widespread. The aim of this study was to investigate the effect of obesity on bone, utilizing a diet-induced obese mouse model, and to explore the role of free fatty acids (FFAs) in the osteogenesis/adipogenesis of mouse bone marrow-derived mesenchymal stem cells (BMSCs). An obese mouse model was established by a high-fat diet (HFD). Proximal femurs were collected at sacrifice, and bone mineral density (BMD) in the proximal femurs was measured by dual-energy X-ray absorptiometry. Bone histomorphometry was performed using undecalcified sections of the proximal femurs. The effect of obesity on the differentiation of mouse BMSCs was assessed by colony formation assays and gene expression analysis. In vitro, various osteogenic and adipogenic genes were determined by real-time quantitative PCR in mouse BMSCs after exposure to conditioned medium (CM) from FFA-treated 3T3-L1 adipocytes. Western blotting was further performed to analyze the representative protein expression of PPARγ and Runx2. BMD and trabecular thickness were significantly greater in the HFD mice than in the control mice. CFU-osteo assay showed significantly increased osteogenesis of BMSCs. The mRNA level of Runx2 was significantly higher, while PPARγ and Pref-1 were significantly lower in BMSCs from the HFD mice compared to the control mice. In mouse BMSCs, the Sox9 and Runx2 genes were significantly up-regulated after exposure to CM from FFA-treated adipocytes, while PPARγ and CEBP-α were significantly down-regulated. Osteogenesis was significantly increased, while adipogenesis was significantly decreased. In conclusion, HFD-induced obesity may play a protective role in bone formation by concomitantly promoting osteogenic and suppressing adipogenic differentiation of BMSCs through factors secreted by FFA-treated adipocytes.